2014
DOI: 10.1021/mp5000086
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Derivative KMUP-1 Reduces Inflammation and Hyperalgesia in a Bilateral Chronic Constriction Injury Model by Suppressing MAPK and NFκB Activation

Abstract: Neuropathic pain is characterized by spontaneous pain, hyperalgesia, and allodynia. The aim of this study was to investigate whether KMUP-1 (7-[2-[4-(2-chlorobenzene)piperazinyl]ethyl]-1,3-dimethylxanthine) could improve pain hypersensitivity and reduce inflammatory mediators, and also explore possible mechanisms in the rat sciatic nerve using bilateral chronic constriction injury (CCI) to induce neuropathic pain. Sprague-Dawley rats were randomly divided into four groups: Sham, Sham+KMUP-1, CCI, and CCI+KMUP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…In addition, previous studies have shown that an increase in MAPK/ErK is associated with up-regulated NADPH oxidase and oxidative stress (Morales et al 2014;Simões et al 2015). As a result, nNOS and other antioxidant (induced nitric oxide synthase and Cyclooxygenase) systems are depleted leading to an increase in inflammation through oxidative stress (Zhang et al 1998;DiCarlo et al 2002;Dai et al 2014).…”
Section: Igf-1r Signaling In Ang Ii-induced Pvn Inflammationmentioning
confidence: 99%
“…In addition, previous studies have shown that an increase in MAPK/ErK is associated with up-regulated NADPH oxidase and oxidative stress (Morales et al 2014;Simões et al 2015). As a result, nNOS and other antioxidant (induced nitric oxide synthase and Cyclooxygenase) systems are depleted leading to an increase in inflammation through oxidative stress (Zhang et al 1998;DiCarlo et al 2002;Dai et al 2014).…”
Section: Igf-1r Signaling In Ang Ii-induced Pvn Inflammationmentioning
confidence: 99%
“…In our experiments, we have shown that the ERK1/2 phosphorylation is increased on day 7 after CCI [24,129], and this is correlated with enhanced glial cell activation [24]. These results suggest that ERK is essential for the intracellular signaling that leads to the production of various nociceptive factors, including cytokines such as TNFα and IL-1β and the enzymes COX-2, iNOS, and nNOS, that participate in the intensification of the neuropathic pain sensations [24,127, 129,156]. Previous studies have demonstrated that the administration of MEK-ERK pathway inhibitors such as PD198306 [157], U0126 [23,155], and PD98059 [123,127,129] reduce the nociceptive behavior in animal models of neuropathic pain, such as CCI, SNL and SCI.…”
Section: Mitogen-activated Protein Kinase (Mapk)mentioning
confidence: 99%
“…When stimulated by appropriate signals, trimeric IKK is activated and phosphorylates IκB, which leads to its ubiquitination and degradation [51] . The liberated reactive NF-κB translocates to the nucleus and targets specific genes that are involved in chronic pain [10,14,52,53] . The algogenic effect of NF-κB has also been identified in BCP animals.…”
Section: Bcp Induced By Walker 256 Mammary Carcinoma Cell Inocula Tionmentioning
confidence: 99%
“…Moreover, nuclear factor kappa B (NF-κB), an important transcriptional factor mediating cytokine production [8,10,11] , is activated in spinal astrocytes during a chronic pain state [8,12] .…”
Section: Introductionmentioning
confidence: 99%